ADVERB OF TIME IN ARABIC SIMPLE SENTENCE - Muhammad Ivan Fauzi; Deli Nirmala; Agus Subiyanto (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2020)
This research aims to describe the pattern of Arabic simple sentences attached by adverb of time and the distribution of the adverb of time in Arabic simple sentences. The research data are in the form of a simple sentence, which contains adverb of time from a paper in the book Al-Arabiyah Baina Yadaik Volume 4a by Al-Fauzan, et al. (2014). The data collection was carried out using the observation method. The analysis of adverb of time in Arabic simple sentence was done by a tree diagram with the guidelines proposed by Chomsky (2002). The results showed that the adverb of time is inherent in verbs and was only found in the original verb and not a derivational verb. In addition, the sentence patterns of Arabic simple sentence attached by adverb of time consist of PS, SP, SPO, and PSO. The researchers also found the distribution of adverbs of time inside the predicate, behind the object, in front of the predicate, and behind the subject.